Perbaikan Lambung Kapal KM. Harima PT. CSFI-Cilacap - Aris Sasongko Dwiono; Andi Hendrawan; Sri Pramono (Dinamika Bahari, 2021)
The purpose of a ship is for the transportation or transfer of goods, but what is no less important is safety. Therefore checking every part is very important. Repair of the hull is mandatory because damage to the hull can result in imbalance in ship operations and even ship accidents. This study aims to describe the repair of the ship's hull on the KM. Harima PT. CSFI Cilacap. The study used a survey method by observing and being directly involved in the ship repair process. Improvements that are in accordance with the research objectives are repairing the ship's hull KM Harima. The results show that ship repair is carried out through checking, welding, welding, or painting.